2017
DOI: 10.1101/238311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanical microenvironment regulates ovarian cancer cell morphology, migration, and spheroid disaggregation

Abstract: There is growing appreciation of the importance of the mechanical properties of the tumor microenvironment on disease progression. However, the role of extracellular matrix (ECM) stiffness and cellular mechanotransduction in epithelial ovarian cancer (EOC) is largely unknown. Here, we investigated the effect of substrate rigidity on various aspects of SKOV3 human EOC cell morphology and migration. Young's modulus values of normal mouse peritoneum, a principal target tissue for EOC metastasis, were determined b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 114 publications
0
29
0
Order By: Relevance
“…Cancer cells are versatile cell types (Alamoud & Kukuruzinska, 2018) that their morphology and functional features are highly influenced from signals within the TME (McKenzie et al, 2018). Cancer cells and cellular components of the stroma of tumor coevolve in functioning to promote malignancy (McKenzie et al, 2018). In initial phases of tumorigenesis, cancer cell release growth factors for stimulating stroma production (Dauer et al, 2017), indicating intricate link between cancer cells with cells within the tumor stroma for shaping the behavior of both stroma cells and cancer cells.…”
Section: Cancer Cellsmentioning
confidence: 99%
“…Cancer cells are versatile cell types (Alamoud & Kukuruzinska, 2018) that their morphology and functional features are highly influenced from signals within the TME (McKenzie et al, 2018). Cancer cells and cellular components of the stroma of tumor coevolve in functioning to promote malignancy (McKenzie et al, 2018). In initial phases of tumorigenesis, cancer cell release growth factors for stimulating stroma production (Dauer et al, 2017), indicating intricate link between cancer cells with cells within the tumor stroma for shaping the behavior of both stroma cells and cancer cells.…”
Section: Cancer Cellsmentioning
confidence: 99%
“…In this study, we developed a 3D culture method to better mimic the aggregate formation observed within the ascites fluid and responsible for short term peritoneal carcinomatosis. We used ovarian tumour cells SKOV-3 coming from ascites and realized tumourospheres in round-bottomed plates treated to prevent cell adhesion (47). After only a few hours, ovarian tumour cells form round or elliptical structures typically corresponding to those described in the literature (48), reproduced as well with 3D culture of patients (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Previously, we showed that efficient migration of SKOV-3 human ovarian cancer cells requires localized PKA activity within the leading edge (32). More recently, we demonstrated that SKOV-3 cell migration is also governed by the mechanical microenvironment; specifically, that cell contractility and migration positively correlate with ECM stiffness and that directional increases in ECM tension promote SKOV-3 cell durotaxis (27). In the present work, we explored the possibility that localized PKA activity in migrating cells might be regulated by mechanical signaling and cell-matrix tension.…”
Section: Introductionmentioning
confidence: 93%
“…In further consideration of what might regulate PKA activity during migration, we began to consider a cellular characteristic that is dependent on integrin-mediated adhesion, intrinsic to many cells across many modes of migration, and not typically associated with cell spreading -namely, actomyosin-dependent cellular contractility (1,13,17,50,51). Intracellular contractile forces regulate diverse aspects of signaling and cytoskeletal dynamics during cell migration (4,13,(20)(21)(22) and, importantly, these forces tend to be highest within the leading edge (23)(24)(25)(26)(27), placing them in the correct subcellular location to affect PKA activity.…”
Section: Leading Edge Pka Activity Is Regulated By Actomyosin Contracmentioning
confidence: 99%
See 1 more Smart Citation